Polycrystalline boron-doped diamond with an oxygen-terminated surface channel as an electrolyte-solution-gate field-effect transistor for pH sensing. (10th September 2016) - Shintani, Yukihiro; Ibori, Shoji; Igarashi, Keisuke; Naramura, Takuro; Inaba, Masafumi; Kawarada, Hiroshi
Abstract: A polycrystalline boron-doped diamond (BDD) electrolyte solution-gate field effect transistor (SGFET) for use as a pH sensor was developed. The polycrystalline diamond films with a boron-doped layer possessed semiconducting properties that were comparable to hydrogen-terminated non-doped diamond. The hydrogen-terminated BDD surface was successfully transferred to a partially oxygen-terminated surface by ozone exposure, and its SGFET current–voltage (I–V) characteristics were evaluated with bias voltages within the potential window of diamond. The drain-source current(Ids)–drain-source voltage(Vds) characteristics showed pinch-off and saturation. In addition, they stably operated in electrolyte solutions with pH values from 2 to 12. The transfer characteristics exhibited a pH sensitivity of approximately 30 mV/pH, which is comparable with the pH sensitivity of the conventional oxygen-terminated non-doped SGFET and the single-crystal BDD SGFET investigated in our previous work. Furthermore, the BDD SGFET exhibited improved long-term stability, and the coefficient of variation (CV) of Ids for 10 months was up to 10%.